Magnetic monopoles and hyperbolic three-manifolds - Braam, P (1987)
Let M = H3/andGamma; be a complete , non-compact , oriented geometrically finite hyperbolic 3-manifold without cusps. By constructing a conformal compactification of M x S1 we functorially associate to M an oriented , conformally flat , compact 4-manifold X (without boundary) with an S1-action. X determines M as a hyperbolic manifold. Using our functor and the differential geometry of conformally flat 4-manifolds we prove that any andGamma; as above with a limit set of Hausdorff dimension andle;1 is Schottky , Fuchsian or extended Fuchsian. Furthermore , the Hodge theory for H2 (X;and#8477;) carries over to H1(M,anddelta;M;and#8477;) and H2(M;and#8477;) which correspond to the spaces of harmonic L2-forms of degree 1 and 2 on M. Comparison of lattices through the Hodge star gives an invariant h(M) andisin; GL(H2(M;and#8477;)/GL(H2(M;and#8484;)) of the hyperbolic structure. Secondly we pay attention to magnetic monopoles on M which correspond to S1invariant solutions of the anti-self-duality equations on X. The basic result is that we associate to M an infinite collection of moduli spaces of monopoles , labelled by boundary conditions. We prove that the moduli spaces are not empty (under reasonable conditions), compute their dimension , prove orientability , the existence of a compactification and smoothness for generic S1-invariant conformal structures on X. For these results one doesn't need a hyperbolic structure on M , the existence of a conformal compactification X suffices. A twistor description for monopoles on a hyperbolic M can be given through the twistor space of X , and monopoles turn out to correspond to invariant holomorphic bundles on twistor space. We analyse these bundles. Explicit formulas for monopoles can be found on handlebodies M , and for M = surface x and#8477; we describe the moduli spaces in some detail.